Integrated Clonal Accelerated Mutation Evolutionary Programming for Composite Compensation in Power System - Ismail S.A.; Musirin I.; Mansor M.H.; Hamid Z.A.; Jelani S.; Kumar A.V.S. (American Institute of Physics, 2025)
Increasing load in a traditional transmission system has led to the increase of current flow which also increases the I2R loss leading to monetary losses in the power system community. This will also affect the economic status of the utility which may require the utility to take possible appropriate remedial action. Thus, a compensation process can be performed to alleviate the high current flow which in turn reduces the monetary losses that can be experienced by the utility. This paper presents Multi Load Variability for Composite Compensation in Loss Control Scheme. In this study a new optimization technique termed Integrated Cloning Accelerated Mutation Evolutionary Programming (ICAMEP) is proposed to optimize the location and sizing for composite compensation in power transmission system for loss control scheme. Several variations in the loading variability were conducted to evaluate the effect of reactive power changes which influence loss value in power system. The effectiveness of the proposed ICAMEP algorithm was compared with respect to the traditional evolutionary programming (EP) and artificial immune system (AIS) optimization techniques for performance comparisons. Results from ICAMEP outperformed AIS and EP in terms of achieving lower transmission loss through the validation process in the IEEE 30-Bus Reliability Test System (RTS). This will benefit power system operators and planners for their expansion planning efforts. ? 2024 American Institute of Physics Inc.. All rights reserved.